Global financial crisis and monetary policies of central banks (examples of chosen countries) - Fajnor, Tomáš (2010)
The purpose of this Master's thesis is divided into two steps. The first step sums up all the relevant theory about financial crises and monetary policies. The second step analyzes not only the past but focuses mainly on the global financial crisis which started in 2007. The cornerstones of this analytical bloc are monetary policies of central banks in China, Venezuela, Denmark and the Czech Republic. Two hypotheses are stated in the beginning of this Master's thesis. These focus on fixed exchange rate regimes and foreign exchange reserves. The analytical part of Master's thesis tries to prove whether these hypotheses can be marked as valid or invalid.